Long term complete response of advanced hepatocellular carcinoma to glypican-3 specific chimeric antigen receptor T-Cells plus sorafenib, a case report - Sun, Hongwei; Xing, Chongyun; Jiang, Songfu; Yu, Kang; Dai, Shengjie; Kong, Hongru; Jin, Yuepeng; Shan, Yunfeng; Yang, Wenjun; Wang, Zhen; Xiao, Jun; Wang, Huamao; et al. (Frontiers in Immunology, 2022)
The clinical efficacy of current therapies for Hepatocellular carcinoma (HCC) are unsatisfactory. In recent years, chimeric antigen receptor (CAR) T-cell therapies have been developed for solid tumors including advanced HCC (aHCC) , but limited progress has been made. Glypican-3 is a promising immunotherapeutic target for HCC since it is specifically highly expressed in HCC. A previous study indicated that GPC3-targeted CAR T-(CAR-GPC3) cells were well-tolerated and had prolonged survival for HCC patients and that Sorafenib could increase the antitumor activities of CAR-GPC3 T-cells against HCC in mouse models. Here, we report a patient with aHCC who achieved a complete response (CR) and a long survival period after the combination therapy of CAR-GPC3 T-cell plus sorafenib. A 60-year-old Asian male diagnosed with hepatitis B virus (HBV) related HCC developed liver recurrence and lung metastasis after liver tumor resection and trans-arterial chemoembolization therapy. The patient also previously received microwave ablation therapy for lung metastasis. After the enrollment, the patient underwent leukapheresis for CAR-GPC3 T-cells manufacturing. Seven days after leukapheresis, the patient started to receive 400 mg of Sorafenib twice daily. The patient received 4 cycles of CAR-GPC3 T cells (CT011) treatment and each cycle was divided into two infusions. Prior to each cycle of CT011 treatment, lymphodepletion was performed. The lymphodepletion regimen was cyclophosphamide 500 mg/m2/day for 2 to 3 days, and fludarabine 20-25 mg/m2/day for 3 to 4 days. A total of 4×109 CAR-GPC3 T cells were infused. The CT011 plus Sorafenib combination therapy was well tolerated. All the ≥ grade 3 AEs were hematological toxicities which were deemed an expected event caused by the preconditioning regimen. This patient obtained partial responses from the 3rd month and achieved CR in the 12th month after the first cycle of CT011 infusion according to the RECIST1.1 assessment. The tumor had no progression for more than 36 months and maintained the CR status for more than 24 months after the first infusion.